2012
DOI: 10.1051/mmnp/20127603
|View full text |Cite
|
Sign up to set email alerts
|

Oscillations in Functional Structural Plant Growth Models

Abstract: Abstract. The dynamic model of plant growth GreenLab describes plant architecture and functional growth at the level of individual organs. Structural development is controlled by formal grammars and empirical equations compute the amount of biomass produced by the plant, and its partitioning among the growing organs, such as leaves, stems and fruits. The number of organs initiated at each time step depends on the trophic state of the plant, which is evaluated by the ratio of biomass available in plant to the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…Kang et al (2011) found correlations between fruit-set probabilities and supply-to-demand ratio on tomato plants but the resulting relationship was not implemented in the model: fruit position was forced as observed. Mathieu et al (2012) reported that periodic fruit-set patterns can be simulated in an FSPM when it is controlled by sourcesink ratio: oscillations can be generated for certain ranges of parameter values, a pattern often observed in particular in fruit trees. Using a GL4-like model for grapevine but with an estimation procedure that relied for some part on a deterministic version of the model and that did not consider the average age of individual phytomers, Pallas et al (2010) found that the rate of phytomer appearance according to thermal time was strongly affected by the plant's trophic status.…”
Section: Use Of Q/d Ratio As a Regulating Variablementioning
confidence: 99%
“…Kang et al (2011) found correlations between fruit-set probabilities and supply-to-demand ratio on tomato plants but the resulting relationship was not implemented in the model: fruit position was forced as observed. Mathieu et al (2012) reported that periodic fruit-set patterns can be simulated in an FSPM when it is controlled by sourcesink ratio: oscillations can be generated for certain ranges of parameter values, a pattern often observed in particular in fruit trees. Using a GL4-like model for grapevine but with an estimation procedure that relied for some part on a deterministic version of the model and that did not consider the average age of individual phytomers, Pallas et al (2010) found that the rate of phytomer appearance according to thermal time was strongly affected by the plant's trophic status.…”
Section: Use Of Q/d Ratio As a Regulating Variablementioning
confidence: 99%
“…We focus on Cecropia obtusa Trécul (Urticaceae), a widespread Guiana shield generalist species, capable of growing on both FS and WS, and displaying perennial growth marks, which allow for an analysis of life history based on architecture analysis (growth, branching, flowering) through time, making C. obtusa a model species for tree architecture and growth (Heuret et al 2002;Zalamea et al 2008;Mathieu et al 2012;Letort et al 2012). We measured commonly used functional leaf and wood traits, coupled with the growth trajectory (i.e.…”
Section: Introductionmentioning
confidence: 99%